Streptomyces in Mangrove Ecosystems: Ecological Roles and Biotechnological Opportunities - Pambayun Faqih, Dhiajeng; Retnowati, Wiwin (CV. Publikasi Indonesia, 2025)
The mangrove ecosystem, a transitional zone between terrestrial and marine environments, is known for its high salinity, low pH, and limited oxygen availability, creating challenging conditions for microbial life. Among the diverse microorganisms present, Streptomyces plays a crucial role due to its ability to produce bioactive compounds, including antibiotics, anticancer agents, and antioxidants. In nutrient cycling, Streptomyces decomposes complex organic matter into simpler compounds, enhancing nutrient availability. Its role in bioremediation is also notable, with the capacity to degrade pollutants such as hydrocarbons and heavy metals, maintaining environmental quality. In agriculture, Streptomyces acts as both a biocontrol agent and a biofertilizer by producing plant hormones like Indole-3-Acetic Acid (IAA) and gibberellins, improving plant growth and resilience. Despite its potential, challenges in isolation, cultivation, and antibiotic resistance remain significant, especially in extreme environments like mangroves. However, advancements in metagenomics, co-cultivation, and bioinformatics provide innovative solutions. Metagenomics allows the discovery of previously undetectable biosynthetic genes, while co-cultivation stimulates the production of novel secondary metabolites. Bioinformatics facilitates gene function prediction and genetic engineering to optimize bioactive compound production. These technologies offer promising avenues to enhance the exploration and utilization of Streptomyces for sustainable applications in medicine, agriculture, and environmental management.